Cry from the deep : the sinking of the Kursk, the submarine disaster that riveted the world and put the new Russia to the ultimate test /: the sinking of the Kursk, the submarine disaster that riveted the world and put the new Russia to the ultimate test. (2005 ©2004) - Unknown
No abstract available